Identification of students' mental models about the milk transformation in yogurt - Muñoz-Campos, Verónica; Franco-Mariscal, Antonio Joaquín; Blanco-López, Ángel (My University, 2017)
A review of the scientific literature reveals that there are still few researches on the conceptions of secondary school students about chemical reactions involving microorganisms, especially those related to the mental models that students use in their explanations. This paper describes a study concerning the different mental models related to the milk transformation into yogurt with 83 students from a Spanish secondary school of 8th and 9th grade (13-16 years) developed in the framework of a research that intends to use the elaboration of this product as a context for the teaching and learning of chemical reactions through modeling approaches. In order to identify the mental models of the students, in this paper we consider the milk transformation into yogurt as a process in which its main components are: the entities involved (milk and bacteria), the interaction between them and the result (yogurt). A simplified school model of this process would involve students considering that bacteria use the sugar in milk to transform it into lactic acid through a chemical reaction to obtain the necessary energy. Using this scheme in interaction with the students' answers, the underlying mental models were identified. Although almost half of the students showed great difficulties explaining the process, five models have been identified. Students often consider the milk transformation into yogurt primarily as a physical process of agglutination or change of state. These models are far from a school model of reference in which the bacteria have a fundamental role in the transformation of milk into yogurt by a chemical reaction.
Keywords: Ciencias - Estudio y enseñanza; Mental models; Chemical reactions; Microorganisms